SEBARAN BANGUNAN PILLBOX SEBAGAI STRATEGI PERTAHANAN JEPANG DI TELUK AMBON - Muhammad Al Mujabuddawat; Wuri Handoko (Balai Arkeologi Bali, 2018)
One characteristic of the Japanese defense system is the existence of pillboxes. During the Japanese occupation of Ambon Island, the construction of the pillboxes was carried out in massive numbers as a defense strategy to anticipate attacks by the Allies who wanted to retake Ambon Island territory. The purpose of this study was to determine the distribution pattern of Pillboxes and analyze the distribution of Pillboxes as part of the Japanese defense strategy in defending Ambon Bay. The data collection method uses the field observation method along the coast of the Ambon Bay which is the entrance of the sea traffic and airlines. This location is the center of settlements and government so that almost all strategic infrastructure is in this region — spatial data obtained from each pillbox object coupled with the Architectural Documentation Center (PDA) inventory data in 2007, then associated with related literature data, processed using Geographic Information System applications to produce the descriptive analysis. The results of this study indicate that the distribution of pillboxes location is generally divider into coastal and hilly locations and there are concentrations in strategic areas. The general conclusion of this study is the pillboxes placement strategy is an effective strategy both in attack and defense. Salah satu ciri khas dari sistem pertahanan Jepang yaitu keberadaan pillbox. Pada masa pendudukan Jepang di Pulau Ambon, pembangunan pillbox dilakukan dalam jumlah masif sebagai strategi pertahanan untuk mengantisipasi serangan Sekutu yang ingin merebut kembali wilayah Pulau Ambon. Tujuan penelitian ini adalah untuk mengetahui pola sebaran Pillbox dan menganalisis sebaran Pillbox sebagai bagian dari bentuk strategi pertahanan Jepang dalam mempertahankan Teluk Ambon. Metode pengumpulan data menggunakan metode observasi lapangan di sepanjang pesisir Teluk Ambon yang merupakan pintu masuk jalur laut dan udara. Lokasi ini merupakan pusat permukiman dan pemerintahan, sehingga hampir seluruh infrastruktur strategis berada di wilayah ini. Data spasial yang diperoleh dari setiap objek pillbox ditambah dengan data inventaris Pusat Dokumentasi Arsitektur (PDA) tahun 2007, lalu dikaitkan dengan data literatur terkait, diolah dengan menggunakan aplikasi Sistem Informasi Geografis untuk menghasilkan analisa deskriptif. Hasil penelitian ini menunjukkan bahwa sebaran lokasi pillbox secara umum terbagi atas lokasi pantai dan perbukitan serta terdapat konsentrasi pillbox di lokasi strategis. Kesimpulan umum dari penelitian ini adalah strategi penempatan pillbox merupakan strategi yang efektif baik dalam menyerang maupun bertahan.